Article manufacturing method
Patent Information
- Application Number
- JP2024230533
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-07
AI Technical Summary
【0012】 本発明によれば、基材と、その表面上に形成された焼結体層とを備える物品において、焼結体層の導電性、基材に対する焼結体層の密着性、及び配線間の絶縁信頼性を高水準で満たす物品の製造方法が提供される。
Smart Images

Figure 2025031985000006 
Figure 2025031985000007 
Figure 2025031985000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an article. [Background technology]
[0002] A method known as a printed electronics method is known as a method for forming a circuit pattern (see, for example, Patent Documents 1 and 2). This method includes a step of forming a pattern made of ink, paste, etc. containing metal particles on a substrate by inkjet printing, screen printing, dispense printing, etc., and a step of forming a conductive circuit pattern by heating the pattern containing metal particles. The metal particles contained in the ink or paste are sintered by heat to form a sintered layer, thereby exhibiting conductivity.
[0003] In recent years, from the viewpoint of miniaturization and weight reduction of wiring, attention has been focused on molded interconnect devices (hereinafter, sometimes referred to as "MIDs"). MIDs are components in which wiring is formed directly on a molded body having a three-dimensional surface such as an uneven surface or a curved surface, and are used in various fields, for example, by mounting electronic components on the wiring using solder. According to the formation technology of MIDs, it is possible to manufacture a structure in which wiring is formed in the dead space of a device, a structure in which a harness is removed, etc., so that it is possible to reduce the weight of in-vehicle components and to miniaturize smartphones, etc. As one aspect of the formation technology of MIDs, the Laser Direct Structuring method (hereinafter, sometimes referred to as "LDS method") is known. The LDS method includes a step of producing a molded body containing metal particles, a step of making the metal particles conductive by irradiating a laser to an area on the surface of the molded body where a circuit is to be formed, and a step of forming a circuit by performing electroless plating on the conductive part on the surface of the molded body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-072418 A [Patent Document 2] JP 2014-148732 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the printed electronics method, there is a trade-off between the adhesion of the sintered body layer constituting the circuit pattern to the substrate and the electrical conductivity of the sintered body layer. In other words, when a binder resin for improving the adhesion of the sintered body layer is mixed with metal particles in the ink or paste, the electrical conductivity of the sintered body layer tends to decrease. In this respect, there is room for improvement in the conventional printed electronics method.
[0006] Meanwhile, according to the research of the present inventors, it was found that by performing a roughening treatment on the surface of a substrate, the sintered body layer formed on the roughened portion subjected to the roughening treatment has increased physical interlocking with the roughened portion of the substrate, thereby improving adhesion.
[0007] On the other hand, the inventors have further studied and found the following problems. FIG. 4(a) is a cross-sectional view showing a sintered body layer in a processed substrate in which the entire surface of the substrate has been roughened, and FIG. 4(b) is a cross-sectional view showing a sintered body layer in a processed substrate in which the entire surface of the substrate has been roughened. That is, when the entire surface of the substrate is roughened, the portion in which the sintered body layer is not formed also becomes the roughened portion 2a. The roughened portion 2a exhibits high adhesion to the sintered body layer, but tends to spread due to capillary action. Therefore, when forming a metal particle-containing layer, which is a precursor of the sintered body layer, for example, when a composition containing metal particles is applied to form the sintered portion 3, the composition spreads to areas other than the desired area, and, for example, as shown in 3a in FIG. 4(a), the line width becomes thicker, making it difficult to form fine wiring, and the insulation reliability between wirings after sintering may decrease (see FIGS. 4(a) and (b)).
[0008] In addition, when a composition containing metal particles applied in a reducing formic acid atmosphere is fired, the metal-containing component, which is a reaction product between the metal particles and formic acid, may sublimate and diffuse to areas other than the applied area. In this case, if areas other than the desired area are roughened, the sublimated components may easily adhere to the substrate, resulting in a problem of reduced insulation reliability between wiring after sintering.
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a method for manufacturing an article comprising a base material and a sintered body layer formed on the surface of the base material, which satisfies high levels of electrical conductivity of the sintered body layer, adhesion of the sintered body layer to the base material, and insulation reliability between wiring. [Means for solving the problem]
[0010] One aspect of the present invention relates to a method for producing an article, the method for producing the article comprising the steps of: selectively roughening a portion of a surface of a base material to obtain a processed base material having a roughened portion that has been roughened and a non-roughened portion that has not been roughened, forming a metal particle-containing layer on the processed base material using a composition containing metal particles so as to cover at least a portion of the roughened portion, and sintering the metal particles in the metal particle-containing layer to form a sintered layer.
[0011] According to this method for producing an article, the adhesion of the sintered body layer to the substrate and the conductivity of the sintered body layer can be improved. In addition, according to this method for producing an article, a part of the surface of the substrate is selectively roughened, and a composition containing metal particles is used to cover at least a part of the roughened part, so that the wetting and spreading of the composition and the adhesion and spreading due to the sublimation of the metal-containing component during firing can be suppressed. Therefore, the deterioration of the insulation reliability between wirings can be prevented. Effect of the Invention
[0012] According to the present invention, there is provided a method for manufacturing an article comprising a substrate and a sintered body layer formed on the surface thereof, which satisfies high levels of electrical conductivity of the sintered body layer, adhesion of the sintered body layer to the substrate, and insulation reliability between wiring. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a perspective view showing an article obtained by a method for producing an article according to one embodiment. [Diagram 2] 2(a), 2(b), and 2(c) are cross-sectional views that diagrammatically show steps of a method for producing an article according to one embodiment. [Diagram 3] 3(a) and 3(b) are cross-sectional views that diagrammatically show steps of a method for manufacturing an article according to one embodiment. [Figure 4] FIG. 4(a) is a cross-sectional view showing a schematic diagram of a sintered body layer in a processed substrate in which a roughening treatment has been applied to the entire substrate surface, and FIG. 4(b) is a cross-sectional view showing a schematic diagram of a sintered body layer in a processed substrate in which a roughening treatment has been applied to only a portion of the substrate surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiment for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values and their ranges, and they do not limit the present invention.
[0015] In this specification, the term "process" includes processes that are independent of other processes, as well as processes that cannot be clearly distinguished from other processes, as long as the purpose of the process is achieved. In this specification, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In a numerical range described in stages in this specification, the upper limit or lower limit described in one numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In addition, in a numerical range described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an example. In this specification, the content or amount of each component in a composition means the total content or amount of the multiple substances present in the composition, unless otherwise specified, when multiple substances corresponding to each component are present in the composition.
[0016] <Articles and their manufacturing methods> FIG. 1 is a perspective view showing an article obtained by a method for producing an article according to an embodiment. FIG. 2(a), FIG. 2(b), and FIG. 2(c) are cross-sectional views that typically show steps in a method for producing an article according to an embodiment. FIG. 3(a) and FIG. 3(b) are cross-sectional views that typically show steps in a method for producing an article according to an embodiment. As shown in FIG. 1, the article 1 includes a processed substrate 2A and a sintered body layer 3 provided on the processed substrate 2A. The processed substrate 2A is a substrate 2 in which a part of the surface thereof is selectively roughened, and has a roughened part 2a that has been roughened and a non-roughened part 2b that has not been roughened (see FIG. 2(c)). The sintered body layer 3 is formed on the processed substrate 2A so as to cover at least a part of the roughened part 2a (see FIG. 3(b)).
[0017] The shape of the substrate 2 is appropriately selected depending on the application. The substrate 2 may be, for example, a three-dimensional object having a three-dimensional shape such as a concave-convex shape. The substrate 2 is, for example, produced by molding a resin using a mold. The resin constituting the substrate 2 may be a resin having low heat resistance (for example, a resin having a glass transition temperature and / or a 5% thermal weight loss temperature described later), for example, a thermoplastic resin. The thermoplastic resin may be a polyolefin such as polyethylene, polypropylene, polymethylpentene, polycarbonate, acrylonitrile butadiene styrene resin, polystyrene, polyphenylene sulfide, polyethylene terephthalate, polyethylene naphthalate, liquid crystal plastic, or the like. The thermoplastic resin may be a mixture of two or more of these or a copolymer containing the molecular structure of these. The resin constituting the substrate is preferably at least one selected from the group consisting of polypropylene, polycarbonate, acrylonitrile butadiene styrene resin, polystyrene, polyphenylene sulfide, polyethylene terephthalate, polyethylene naphthalate, and liquid crystal plastic.
[0018] The glass transition temperature of the resin may be 150° C. or lower, 120° C. or lower, or 80° C. or lower, or may be 30° C. or higher. The glass transition temperature of the resin is measured by dynamic viscoelasticity measurement, specifically, for example, using a dynamic viscoelasticity measuring device, and is measured as the temperature at which tan δ is maximum under conditions of a frequency of 10 Hz, a heating rate of 5° C. / min, and a temperature range of 20 to 260° C.
[0019] The 5% thermal weight loss temperature of the resin may be 400° C. or less, 300° C. or less, 250° C. or less, or 200° C. or less. The 5% thermal weight loss temperature of the resin is defined as the temperature at which the weight of the resin decreases by 5 wt% relative to the weight of the resin at 25° C. (before heating) when the resin is heated from 25° C. at a heating rate of 5° C. / min in a nitrogen atmosphere using a thermogravimetric analyzer (TGA).
[0020] The substrate 2 may contain components other than resin. For example, from the viewpoint of improving heat resistance or strength, the substrate 2 may contain a filler. Examples of the filler include glass, silica, metal oxides, carbon, and minerals.
[0021] The substrate 2 may include electrodes or wiring made of, for example, gold, silver, copper, nickel, palladium, aluminum, etc. The electrodes or wiring may be disposed on the surface of or inside the substrate 2, for example.
[0022] The sintered body layer 3 is formed, for example, on one surface 2f side (upper surface side in FIG. 1) of the processed substrate 2A (substrate 2) so as to cover at least a portion of the roughened portion 2a. That is, the sintered body layer 3 may be formed so as to cover a portion or the entirety of the roughened portion 2a. When the sintered body layer 3 is formed so as to cover the entirety of the roughened portion 2a, a portion of the sintered body layer 3 may be formed on the non-roughened portion 2b (see FIG. 3(b)).
[0023] One surface 2f of the processed substrate 2A (substrate 2) may be a surface having a three-dimensional shape such as an uneven surface, a curved surface, etc. The sintered layer 3 is a layer having electrical conductivity, and may be, for example, wiring that forms an electric circuit (which may be linear when viewed from above).
[0024] The sintered body layer 3 may be a layer containing a copper sintered body. The sintered body layer 3 may be obtained by sintering a composition containing copper particles (details will be described later). The sintered body layer 3 may be, for example, a porous layer. The porosity of the sintered body layer 3 may be 10% or more, 13% or more, or 15% or more, and may be 70% or less, 55% or less, or 40% or less. The porosity of the sintered body layer 3 means the ratio of the area of the non-conductive part where no sintered body is present to the total area of the cross section of the sintered body layer 3, which is obtained by analyzing a cross-sectional image of the sintered body layer 3 observed by a scanning electron microscope, a scanning ion microscope, or the like, using image analysis software.
[0025] The sintered body layer 3 can be a thin-line wiring having a sufficient thickness. The thickness of the sintered body layer 3 may be 1.0 μm or more, 5.0 μm or more, 7.0 μm or more, or 10.0 μm or more, and may be 200 μm or less, 100 μm or less, 60 μm or less, 50 μm or less, or 32 μm or less. The line width of the sintered body layer 3 (the length of the short side direction (the direction perpendicular to the direction in which the wiring extends) of the sintered body layer 3 (wiring) when viewed from above) may be 5 mm or less, 3 mm or less, 1 mm or less, 0.7 mm or less, 0.5 mm or less, 0.4 mm or less, 0.3 mm or less, or 0.2 mm or less.
[0026] Next, a method for manufacturing the article 1 will be described with reference to Fig. 2(a), Fig. 2(b), and Fig. 2(c). The manufacturing method includes a step (first step) of selectively roughening a part of the surface of the base material 2 to obtain a processed base material 2A having a roughened part 2a that has been roughened and a non-roughened part 2b that has not been roughened, a step (second step) of forming a metal particle-containing layer 3p using a composition containing metal particles so as to cover at least a part of the roughened part 2a in the processed base material 2A, and a step (third step) of sintering the metal particles to form a sintered body layer 3. Here, the metal particles may contain a sinterable metal, and may contain, for example, silver (Ag), copper (Cu), palladium (Pd), aluminum (Al), nickel (Ni), zinc (Zn), tin (Sn), bismuth (Bi), indium (In), iron (Fe), etc. The sinterable metal is a metal that can form a sintered body when the metal particles are heated at a temperature lower than the melting point. Hereinafter, a detailed explanation will be given using an example in which the sinterable metal is copper, but in the following description, "copper" may be replaced with "another metal having sinterability."
[0027] (First step) This step is a step of preparing a substrate 2 and selectively roughening a part of the surface of the substrate 2. Here, the surface of the substrate means the surface on which the metal particle-containing layer 3p and the sintered body layer 3 are formed (the surface on which the metal particle-containing layer 3p and the sintered body layer 3 are to be formed), and does not include the surface on which the metal particle-containing layer 3p and the sintered body layer 3 are not arranged. Figures 2(a) and (b) are diagrams showing a step of roughening a part of the surface on the one side 2f side of the substrate 2, and are steps of roughening a part of the surface on the one side 2f side of the substrate 2 (see Figures 2(a) and (b)), and Figure 2(b) is a diagram showing a roughening treatment by a laser 5 as an example of the roughening treatment. By these roughening treatments, a processed substrate 2A having a roughened portion 2a that has been roughened and a non-roughened portion 2b that has not been roughened is obtained (see Figure 2(c)). By using such a processed substrate 2A, the adhesion of the sintered body layer to the substrate can be improved.
[0028] Examples of the roughening treatment include laser irradiation treatment, polishing treatment, sandblasting treatment, wet blasting treatment, flame treatment, corona treatment, plasma treatment, etc. The roughening treatment may be, for example, a molding treatment using a mold with a concave-convex pattern. The roughening treatment can be selected arbitrarily according to the desired characteristics. The roughening treatment may be at least one selected from the group consisting of laser irradiation treatment, polishing treatment, sandblasting treatment, and wet blasting treatment, and is more preferably laser irradiation treatment because fine and selective roughening can be easily performed.
[0029] In the laser irradiation treatment, by selectively irradiating a desired portion of the substrate, fine and selective roughening can be easily performed. In addition, the spot diameter of the laser can be adjusted in micrometer units. Therefore, by using a laser, roughening treatment can be performed with a line width of, for example, 100 μm or less. In addition, even if one surface 2f of the substrate 2 has a three-dimensional shape, selective roughening treatment can be performed.
[0030] As the laser irradiation device, for example, a laser marker used for processing resin or ceramics can be used. As the laser, for example, a CO2 laser (wavelength: 10.6 μm), a near-infrared laser (wavelength: 1064 nm), a visible light laser (wavelength: 532 nm), an ultraviolet laser (wavelength: 355 nm), etc. can be used.
[0031] Examples of parameters for laser irradiation include average laser power (W), frequency (Hz), and scan speed (mm / s). These parameters can be appropriately set according to the shape (line or surface) of the sintered body layer 3 to be formed, the material of the base material 2, and the like. For example, when the base material 2 is irradiated with a laser under predetermined conditions and the roughening is wider than the area to be roughened, measures such as lowering the laser output, increasing the Q-switch frequency, and increasing the scan speed may be taken. According to the study by the present inventors, when the sintered body layer 3 is formed in a planar shape, that is, when the roughening treatment is performed in a planar shape, it is preferable to increase the scan speed compared to when the roughened portion is formed in a linear shape. In addition, when a base material with low thermal conductivity is treated, it is preferable to increase the scan speed because the heat caused by the laser irradiation is less likely to diffuse compared to a base material with high thermal conductivity, and therefore the base material is more likely to be roughened.
[0032] The laser irradiation may be performed while spraying a reducing gas onto the region to be irradiated with the laser, or may be performed in an air atmosphere without spraying such a gas. When a metal electrode is already formed on the resin substrate, it is preferable to perform the laser irradiation in an inert (e.g., nitrogen, argon, etc.) or reducing atmosphere in order to suppress oxidation of the metal electrode.
[0033] In wet blasting, sand blasting, etc., the roughening treatment can be selectively performed on the portion sprayed with an abrasive by spraying. When performing fine treatment, for example, a method is effective in which a protective layer (masking) is placed on the portion of the base material 2 that will become the non-roughened portion 2b by attaching tape, exposing and developing a resist film, etc., and then the roughening treatment is performed on the entire base material 2.
[0034] Polishing can be performed, for example, by rubbing the surface of the substrate with abrasive paper, etc. Polishing can also be performed by using a hand grinder with a long, thin, needle-like tip to perform fine roughening treatment with a width of about 1 mm.
[0035] For example, by placing a protective layer (masking) on the portion of the substrate 2 that will become the non-roughened portion 2b and performing the above-mentioned roughening treatment on the portion where the protective layer is not placed, a processed substrate 2A having a roughened portion 2a that has been subjected to the roughening treatment and a non-roughened portion 2b that has not been subjected to the roughening treatment can be efficiently obtained.
[0036] The roughening treatment is preferably carried out so that the surface roughness Ra (arithmetic mean roughness (JIS B 0601-2001)) of the roughened portion 2a of the processed substrate 2A is in the range of 0.05 to 10.0 μm. From the viewpoints of good adhesion strength and cross-sectional shape of the wiring, the surface roughness of the roughened portion 2a of the processed substrate 2A is more preferably 0.1 to 6.0 μm.
[0037] (Second step) This step is a step of forming a metal particle-containing layer 3p using a composition containing copper particles so as to cover at least a part of the roughened portion 2a of the processed substrate 2A (see FIG. 3(a)). The metal particle-containing layer 3p is formed on the surface of the one side 2f of the processed substrate 2A.
[0038] The metal particle-containing layer 3p can be formed, for example, by a method using an aerosol jet. As the device, a spraying device equipped with an atomizer and a discharge nozzle connected to the atomizer can be used. As such a spraying device, a device to which a known spraying method is applied can be used as it is. Examples of known spraying methods include an aerosol deposition method, a cold spray method, and a thermal spray method.
[0039] The metal particle-containing layer 3p can also be formed by a method using a jet dispenser. As the apparatus, a coating apparatus having a syringe, a discharge nozzle connected to the syringe, and a movable part for discharging the metal particle composition from the nozzle can be used. As such a coating apparatus, an apparatus to which a known coating method is applied can be used as it is.
[0040] The metal particle-containing layer 3p is formed on the processing substrate 2A so as to cover at least a portion of the roughened portion 2a. That is, the metal particle-containing layer 3p may be formed so as to cover a portion or the entirety of the roughened portion 2a. When the metal particle-containing layer 3p is formed so as to cover the entirety of the roughened portion 2a, a portion of the metal particle-containing layer 3p may be formed on the non-roughened portion 2b (see FIG. 3(a)).
[0041] When forming the metal particle-containing layer 3p by the above method, it is preferable to spray or apply the composition in such a manner that the entire roughened portion 2a of the processing substrate 2A is covered. As such a method, for example, a protective layer (masking) is placed on the portion that will become the non-roughened portion 2b, and the composition is sprayed or applied to the roughened portion 2a.
[0042] The composition used in this step (composition for forming a metal sintered body layer) contains at least copper particles, and further contains, for example, a dispersion medium. The copper particles contain copper as a main component from the viewpoint of thermal conductivity and sinterability. The proportion of copper element in the copper particles may be 80 atomic % or more, 90 atomic % or more, or 95 atomic % or more based on all elements excluding hydrogen, carbon, and oxygen. When the element proportion is 80 atomic % or more, the thermal conductivity and sinterability derived from copper tend to be easily expressed.
[0043] The shape of the copper particles is not particularly limited, and examples thereof include spherical, approximately spherical, polyhedral, needle-like, flake-like, and rod-like. The copper particles may contain at least flake-like copper particles, and may further contain other copper particles of different shapes. By containing copper particles of different shapes, cracks in the wiring to be formed tend to be suppressed, and wiring having a sufficient thickness tends to be easily formed. The reason for this is not necessarily clear, but it is thought that this is because copper particles of different shapes complement each other's gaps, and the occurrence of volume reduction in all directions due to fusion between copper particles is suppressed. As a result, it is presumed that cracks are suppressed even in wiring having a sufficient thickness. The combination of different shapes is not particularly limited, and for example, a combination of flake-like copper particles (A1) and spherical copper particles (A2) is preferable.
[0044] The median diameter of the flaky copper particles (A1) is 1.0 μm or more. The lower the heat resistance of the resin substrate, the greater the influence of expansion or contraction and warping due to temperature changes in the firing process, and the more likely the wiring is to crack. The larger the median diameter of the flaky copper particles, the more cracks can be suppressed. From this viewpoint, the median diameter may be 5.0 μm or more or 8.0 μm or more. The upper limit of the median diameter may be 20.0 μm from the viewpoint of easily maintaining good low-temperature sintering properties and coatability. The median diameter of the spherical copper particles (A2) may be 0.1 to 2.0 μm, 0.1 to 1.2 μm, 0.1 to 0.9 μm, or 0.1 to 0.6 μm. By combining the flaky copper particles (A1) and the spherical copper particles (A2) having such a median diameter, the fusion property at low temperatures tends to be more excellent. The median particle size refers to the D50 value (cumulative median of volume distribution) measured using a laser diffraction particle size distribution analyzer (e.g., Submicron Particle Analyzer N5 PLUS (Beckman Coulter)).
[0045] The ratio of the content of the spherical copper particles (A2) to the content of the flaky copper particles (A1) in the composition (content of spherical copper particles (A2) / content of flaky copper particles (A1)) may be 0.25 to 4.0, 0.3 to 3.0, or 0.4 to 2.5. When the content of the spherical copper particles (A2) to the content of the flaky copper particles (A1) is within such a range, cracking tends to be further suppressed.
[0046] The content of the copper particles may be 20 to 90 parts by mass relative to 100 parts by mass of the total composition. The content of the copper particles may be 30 parts by mass or more, 40 parts by mass or more, or 50 parts by mass or more. When the content of the copper particles is 20 parts by mass or more relative to 100 parts by mass of the total composition, wiring having a sufficient thickness tends to be formed. The content of the copper particles may be 85 parts by mass or less, 80 parts by mass or less, 75 parts by mass or less, 70 parts by mass or less, or 65 parts by mass or less. When the content of the copper particles is 85 parts by mass or less relative to 100 parts by mass of the total composition, the dischargeability from the device tends to be better.
[0047] In one embodiment, the copper particles may be copper-containing particles having a core particle containing copper and an organic material that covers at least a part of the surface of the core particle. The copper-containing particles may have, for example, a core particle containing copper and an organic material containing a substance derived from an alkylamine present on at least a part of the surface of the core particle. The alkylamine may be an alkylamine having a hydrocarbon group with 7 or less carbon atoms. Since the chain length of the hydrocarbon group of the alkylamine constituting the organic material is relatively short, the copper-containing particles are thermally decomposed even at a relatively low temperature (for example, 150°C or less), and the core particles are easily fused together. As such copper-containing particles, for example, the copper-containing particles described in JP 2016-037627 A can be suitably used. Note that, from the viewpoint of achieving excellent electrical conductivity, it is preferable that no organic material remains in the sintered body layer 3, and the content of the organic material in the sintered body layer 3 is preferably 3% by mass or less, more preferably 1% by mass or less. According to the manufacturing method of this embodiment, even if the sintered body layer 3 does not contain a binder resin (organic material), excellent adhesion of the sintered body layer 3 to the base material 2 can be achieved.
[0048] The organic matter may contain an alkylamine having a hydrocarbon group with 7 or less carbon atoms. The alkylamine having a hydrocarbon group with 7 or less carbon atoms may be, for example, a primary amine, a secondary amine, an alkylenediamine, etc. Examples of the primary amine include ethylamine, 2-ethoxyethylamine, propylamine, 3-ethoxypropylamine, butylamine, 4-methoxybutylamine, isobutylamine, pentylamine, isopentylamine, hexylamine, cyclohexylamine, heptylamine, etc. Examples of the secondary amine include diethylamine, dipropylamine, dibutylamine, ethylpropylamine, ethylpentylamine, etc. Examples of the alkylenediamine include ethylenediamine, N,N-dimethylethylenediamine, N,N'-dimethylethylenediamine, N,N-diethylethylenediamine, N,N'-diethylethylenediamine, 1,3-propanediamine, 2,2-dimethyl-1,3-propanediamine, N,N-dimethyl-1,3-diaminopropane, N,N'-dimethyl-1,3-diaminopropane, N,N-diethyl-1,3-diaminopropane, 1,4-diaminobutane, 1,5-diamino-2-methylpentane, 1,6-diaminohexane, N,N'-dimethyl-1,6-diaminohexane, and 1,7-diaminoheptane.
[0049] The organic matter coating at least a portion of the surface of the core particle may contain an organic matter other than the alkylamine having a hydrocarbon group with a carbon number of 7 or less. The ratio of the alkylamine having a hydrocarbon group with a carbon number of 7 or less to the total organic matter is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0050] The proportion of the organic material covering at least a part of the surface of the core particle is preferably 0.1 to 20% by mass based on the total of the core particle and the organic material. When the proportion of the organic material is 0.1% by mass or more, sufficient oxidation resistance tends to be obtained. When the proportion of the organic material is 20% by mass or less, it tends to be easy to achieve conductorization at low temperatures. The proportion of the organic material based on the total of the core particle and the organic material is more preferably 0.3 to 10% by mass, and even more preferably 0.5 to 5% by mass.
[0051] The copper-containing particles contain at least copper, and may contain other substances as necessary. Examples of other substances include metals such as gold, silver, platinum, tin, and nickel, or compounds containing these metal elements, reducing compounds or organic substances, oxides, chlorides, and the like. From the viewpoint of forming a conductor with excellent electrical conductivity, the copper content in the copper-containing particles is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The method for producing the copper-containing particles is not particularly limited. For example, the method for producing copper-containing particles disclosed in JP 2016-037626 A can be mentioned.
[0052] The dispersion medium is not particularly limited and can be appropriately selected from organic solvents generally used in the manufacture of conductive inks, conductive pastes, etc. according to the application. The dispersion medium may be used alone or in combination of two or more. From the viewpoint of viscosity adjustment, the dispersion medium may be terpineol, isobornylcyclohexanol, dihydroterpineol, dihydroterpineol acetate, ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, glycerin, tributyrin, acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, propyl acetate, butyl acetate, ethyl lactate, etc. The content of the dispersion medium may be 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more, and 300 parts by mass or less, 200 parts by mass or less, or 150 parts by mass or less, relative to 100 parts by mass of copper particles.
[0053] The composition may further contain other components other than the copper particles and the dispersion medium as necessary. Examples of the other components include silane coupling agents, polymer compounds (resins), radical initiators, reducing agents, rheology modifiers, and the like. Examples of the other components include metal particles other than copper particles. Examples of the other metal particles include aluminum, nickel, tin, bismuth, indium, zinc, iron, silver, gold, palladium, platinum, and the like. From the viewpoint of obtaining sufficient bonding properties, the content of the other metal particles may be less than 20% by mass, and may be 10% by mass or less, based on the total mass of the metal particles contained in the composition. When the other metal particles are contained, the content of the dispersion medium set based on the content of the copper particles can be set based on the content of the copper particles and the metal particles.
[0054] The viscosity of the composition at 25°C can be appropriately set depending on the method of use of the composition, and may be, for example, 10 to 100,000 mPa·s, 100 to 80,000 mPa·s, 500 to 60,000 mPa·s, or 1,000 to 40,000 mPa·s. The viscosity of the composition at 25°C means the viscosity at 25°C measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name: VISCOMETER-TV22, applicable cone-plate rotor: 3°×R17.65).
[0055] The method for producing the composition is not particularly limited, and a method commonly used in the technical field can be used. For example, the composition can be prepared by dispersing copper particles, a dispersion medium, and other components as necessary. For the dispersion treatment, a media dispersing machine such as an Ishikawa type mixer, a planetary centrifugal mixer, an ultra-thin high-speed rotary dispersing machine, a roll mill, an ultrasonic dispersing machine, or a bead mill, a cavitation mixing machine such as a homomixer or a Silverson mixer, or a counter collision method such as an Ultemizer can be used. These methods may also be used in appropriate combination.
[0056] (Third step) This step is a step of sintering the metal particles in the metal particle-containing layer 3p to form the sintered body layer 3 (see FIG. 3(b)). Here, the metal particle-containing layer 3p is heated to thermally decompose the organic matter and fuse the metal particles together to form the sintered body layer 3. The sintered body layer 3 can be said to be a layer made conductive (i.e., a conductor layer). This allows the product 1 to be obtained. The heating temperature for sintering may be, for example, 250°C or less, 230°C or less, or 210°C or less, or 100°C or more, 110°C or more, or 120°C or more. If sintering is performed at such a low temperature, the sintered body layer 3 can be formed without damaging the base material 2 and the processed base material 2A even if the heat resistance of the base material 2 and the processed base material 2A is insufficient. The heating temperature for sintering is usually 100°C or more. In particular, when using copper-containing particles having a core particle containing copper and an organic substance covering at least a portion of the surface of the core particle, the particles can be conductorized at a low temperature, so the heating temperature for forming the conductor layer may be 200°C or less, or 180°C or less.
[0057] The heating temperature for sintering may be constant or may be changed regularly or irregularly. The heating time is not particularly limited and can be selected in consideration of the heating temperature, heating atmosphere, amount of copper-containing particles, etc. The heating method is not particularly limited, and may be, for example, heating by a hot plate, an infrared heater, or a pulse laser.
[0058] The atmosphere in which the metal particle-containing layer 3p is heated is not particularly limited, and may be an inert atmosphere containing nitrogen, argon, etc., or a reducing atmosphere containing a reducing substance such as hydrogen, formic acid, etc. The pressure is not particularly limited, but heating the metal particle-containing layer 3p in a reduced pressure atmosphere tends to promote the formation of a conductor at a lower temperature.
[0059] From the viewpoint of low-temperature firing, a reducing atmosphere containing formic acid is particularly preferable.
[0060] The method for producing an article having a sintered body layer (conductor layer) may further include other steps as necessary. Examples of the other steps include a step of removing at least a part of the volatile components in the metal particle-containing layer 3p before heating for sintering the metal particles in the metal particle-containing layer 3p, a step of further heating the formed sintered body layer (conductor layer) in a reducing atmosphere after sintering the metal particles in the metal particle-containing layer 3p to reduce the oxide (copper oxide) contained in the sintered body layer (conductor layer), a step of removing the remaining components in the sintered body layer (conductor layer) by light-firing the sintered body layer (conductor layer), and a step of applying a load to the sintered body layer (conductor layer).
[0061] The article 1 can be suitably used as an MID (sometimes called a molded circuit component, a three-dimensional molded circuit component, a three-dimensional molded circuit component, etc.). Specifically, the article 1 can be suitably used as a smartphone antenna, an in-vehicle wiring, a laminated plate, a solar cell panel, a display, a transistor, a semiconductor package, a multilayer ceramic capacitor, etc. The article 1 can also be used as a member for electrical wiring, a heat dissipation film, a surface coating film, etc.
[0062] Although the embodiment of the present invention has been described, the present invention is not limited to the above embodiment. For example, in the above embodiment, the case where copper particles, which have the advantage of low material cost but are easily oxidized, are used as the metal particles is exemplified, but instead of the copper particles, silver particles, silver-copper particles, silver-palladium particles, tin particles, tin bismuth particles, aluminum particles, or nickel particles may be used. EXAMPLES
[0063] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.
[0064] <Preparation of Composition> A composition for forming a metal sintered body layer was prepared by mixing 70 parts by mass of copper particles (A) shown below and 30 parts by mass of an organic solvent (B) shown below. The median diameter (D50) of the copper particles was measured using a submicron particle analyzer N5 PLUS (Beckman Coulter).
[0065] (Copper particles (A)) As the copper particles (A), a mixture of flaky copper particles (A1) and spherical copper particles (A2) in a ratio of 30:70 (mass ratio) (ratio of the content of spherical copper particles (A2) to the content of flaky copper particles (A1) (content of spherical copper particles (A2) / content of flaky copper particles (A1)): 2.3) was used. Flake-shaped copper particles (A1): Product name: 3L3N, Fukuda Metal Foil and Powder Co., Ltd., Median diameter (D50): 5.0 μm Spherical copper particles (A2): Product name: CH0200, Mitsui Mining & Smelting Co., Ltd., Median diameter (D50): 0.15 μm
[0066] (Organic solvent (B)) As the organic solvent, a mixture of 70 parts by mass of terpineol and 30 parts by mass of tributyrin was used.
[0067] [Example 1] <Preparation of processed substrate> A polypropylene (PP) substrate (size: 30 mm x 30 mm) was prepared, and the PP substrate was subjected to a roughening treatment. Specifically, 2 mm wide tapes were masked on the substrate at 2 mm intervals, and the unmasked substrate surface was rubbed with waterproof abrasive paper (manufactured by Sankyo Rikagaku Co., Ltd., grain size #120) to obtain a processed substrate having a roughened portion and a non-roughened portion. The surface roughness Ra of the roughened portion of the processed substrate was 4.7 μm.
[0068] <Formation of Metal Particle-Containing Layer> The above composition was applied to the processed substrate that was still masked using a squeegee so that the roughened portion was covered. The composition was adjusted so that the thickness of the tape remained on the processed substrate. The tape was then peeled off, and the processed substrate to which the composition had been applied was dried at a temperature of 90° C. for 5 minutes to form a metal particle-containing layer.
[0069] <Formation of sintered layer> Next, the processed substrate having the metal particle-containing layer was heated in a nitrogen atmosphere containing 3% formic acid at a temperature increase rate of 6°C / min up to 110°C and held at 110°C for 60 minutes, thereby obtaining the article of Example 1.
[0070] [Comparative Example 1-1] An article of Comparative Example 1-1 was obtained in the same manner as in Example 1, except that a PP substrate (size: 30 mm×30 mm) that had not been subjected to a roughening treatment was used.
[0071] [Comparative Example 1-2] An article of Comparative Example 1-2 was obtained in the same manner as in Example 1, except that a PP substrate (size: 30 mm×30 mm) whose entire surface had been subjected to a roughening treatment without masking was used.
[0072] [Example 2] <Preparation of processed substrate> A PP substrate (size: 30 mm×30 mm) was prepared and roughened using abrasive paper in lines 1 mm wide and spaced 1 mm apart to obtain a processed substrate having roughened and non-roughened areas.
[0073] <Formation of Metal Particle-Containing Layer> The composition was applied to the obtained processed substrate in a line shape having a line width of 1 mm using a jet dispenser so as to cover the roughened portion, thereby forming a metal particle-containing layer.
[0074] <Formation of sintered layer> A sintered layer was formed in the same manner as in Example 1, and an article of Example 2 was obtained.
[0075] [Comparative Example 2] An article of Comparative Example 2 was obtained in the same manner as in Example 2, except that a PP substrate (size: 30 mm×30 mm) whose entire surface had been roughened using abrasive paper was used.
[0076] [Example 3] <Preparation of processed substrate> A polypropylene (PP) case (size: 70 mm × 100 mm × 30 mm) was prepared. The surface of the PP case was roughened in the same manner as in Example 2 to obtain a processed substrate having L-shaped roughened portions and the other non-roughened portions on two adjacent surfaces.
[0077] <Formation of Metal Particle-Containing Layer> The composition was applied to the obtained processed substrate in a line shape with a line width of 1 mm using a jet dispenser so as to cover the roughened portion, forming a metal particle-containing layer. In the case of a PP case, the composition was continuously applied to two adjacent sides, forming an L-shaped metal particle-containing layer.
[0078] <Formation of sintered layer> A sintered layer was formed in the same manner as in Example 1, and an article of Example 3 was obtained.
[0079] [Comparative Example 3-1] An article of Comparative Example 3-1 was obtained in the same manner as in Example 1, except that a PP case (size: 70 mm×100 mm×30 mm) that had not been subjected to a roughening treatment was used.
[0080] [Comparative Example 3-2] An article of Comparative Example 3-2 was obtained in the same manner as in Example 3, except that a PP case (size: 70 mm×100 mm×30 mm) whose entire surface had been roughened using abrasive paper was used.
[0081] [Example 4] <Preparation of processed substrate> A PP case (size: 70 mm x 100 mm x 30 mm) was prepared. The surface of the PP case was roughened linearly with a line width of 1 mm at intervals of 1 mm by laser irradiation treatment, and a processed substrate having L-shaped roughened areas and other non-roughened areas on two adjacent sides was obtained. A fiber laser processing machine (Gunyucut GT1300R, manufactured by Gunkyo Seisakusho Co., Ltd.) was used as the laser irradiation device, and laser irradiation was performed under the following conditions. Laser: Near infrared laser (wavelength: 1.07μm) Laser average power: 18W Frequency: 500Hz Scan speed: 500~4000mm / s Laser irradiation atmosphere: Air
[0082] <Formation of Metal Particle-Containing Layer> The composition was applied to the obtained processed substrate in a line shape with a line width of 1 mm using a jet dispenser so as to cover the roughened portion, forming a metal particle-containing layer. In the case of a PP case, the composition was continuously applied to two adjacent sides, forming an L-shaped metal particle-containing layer.
[0083] <Formation of sintered layer> A sintered layer was formed in the same manner as in Example 1, and an article of Example 4 was obtained.
[0084] [Comparative Example 4] An article of Comparative Example 4 was obtained in the same manner as in Example 4, except that a PP case (size: 70 mm×100 mm×30 mm) whose entire surface had been subjected to a roughening treatment by similar laser irradiation treatment was used.
[0085] [Example 5] <Preparation of processed substrate> A polyphenylene sulfide (PPS) substrate (size: 30 mm×30 mm) was prepared. The surface of the PPS substrate was subjected to a roughening treatment in the same manner as in Example 4 to obtain a processed substrate having a roughened portion and a non-roughened portion.
[0086] <Formation of Metal Particle-Containing Layer> The composition was applied to the obtained processed substrate in a line shape having a line width of 1 mm using a jet dispenser so as to cover the roughened portion, thereby forming a metal particle-containing layer.
[0087] <Formation of sintered layer> A sintered layer was formed in the same manner as in Example 1, and an article of Example 4 was obtained.
[0088] [Comparative Example 5] An article of Comparative Example 5 was obtained in the same manner as in Example 5, except that a PPS substrate (size: 30 mm×30 mm) whose entire surface had been subjected to a roughening treatment by similar laser irradiation treatment was used.
[0089] <Various evaluations> (Conductivity of sintered layer) The volume resistivity of the formed sintered body layer was calculated from the sheet resistance value measured with a four-point needle sheet resistance meter and the thickness of the sintered body layer measured with a non-contact surface / layer cross-sectional shape measurement system (VertScan, manufactured by Mitsubishi Chemical Systems Corporation). The conductivity of the sintered body layer was evaluated according to the following criteria based on the volume resistivity value. In general, if the volume resistivity is less than 100 μΩ·cm, it can be said that the conductivity is excellent. The results are shown in Tables 1, 2, 3, 4, and 5. A: Less than 10 μΩ·cm. B: 10 μΩ·cm or more and less than 30 μΩ·cm. C: 30 μΩ·cm or more and less than 100 μΩ·cm. D: 100 μΩ·cm or more.
[0090] (Adhesion of sintered layer to substrate) The formed sintered layer was visually observed, scratched with tweezers, and subjected to a tape peeling test to evaluate adhesion. Adhesion was judged according to the following criteria. Adhesion was deemed good when the following criteria A or B was satisfied. The results are shown in Tables 1, 2, 3, 4, and 5. A: No peeling occurred after tape peeling test. B: No peeling occurred after the tweezers scratch test. C: No peeling was observed with the naked eye, but peeling was observed after a scratch test with tweezers. D: Peeling was visually observed.
[0091] (Insulation reliability between wiring) After applying solder resist over the wiring, the resist was hardened by heating in a nitrogen atmosphere at 120°C for 1 hour. Regarding the insulation reliability between wiring, the initial insulation resistance value and the value after migration testing (left for 100 hours under conditions of temperature 85°C, humidity 85%, and 20V application) were measured for 6 samples. 9 The percentage of samples with a resistance of 0.1Ω or more was calculated. The insulation reliability was judged from the obtained percentage according to the following criteria. It is noted that the insulation reliability is good when the following criteria A or B is satisfied. The results are shown in Tables 1, 2, 3, 4, and 5. A: Insulation resistance value 10 9 The proportion of samples with a size of Ω or higher was 6 out of 6 total samples. B: Insulation resistance value 10 9 The proportion of samples with a size of Ω or higher was 5 out of 6 samples. C: Insulation resistance value 10 9 The proportion of samples with a size of Ω or more was 4 or 3 out of the total 6 samples. D: Insulation resistance value 10 9 The proportion of samples with a value of Ω or higher was 2, 1, or 0 out of the total 6 samples.
[0092] [Table 1]
[0093] [Table 2]
[0094] [Table 3]
[0095] [Table 4]
[0096] [Table 5]
[0097] As shown in Tables 1, 2, 3, 4, and 5, the articles of the examples using the processed substrate having a roughened portion that was roughened and a non-roughened portion that was not roughened were excellent in terms of conductivity, adhesion, and insulation reliability. On the other hand, the articles of the comparative examples using the substrate not roughened were insufficient in terms of conductivity, adhesion, and insulation reliability. In addition, the articles of the comparative examples using the processed substrate in which the entire surface was roughened were excellent in terms of conductivity and adhesion, but were insufficient in terms of insulation reliability. From these results, it was confirmed that the articles manufactured by the method for manufacturing an article of the present invention satisfy high levels of conductivity of the sintered body layer, adhesion of the sintered body layer to the substrate, and insulation reliability between wiring. [Explanation of symbols]
[0098] 1...Article, 2...Base material, 2A...Processed base material, 2a...Roughened part, 2b...Non-roughened part, 3...Sintered body layer, 3p...Metal particle-containing layer, 5...Laser.
Claims
[Claim 1] A process of selectively roughening a portion of a surface of a substrate to obtain a processed substrate having a roughened portion that has been roughened and a non-roughened portion that has not been roughened; forming a metal particle-containing layer on the processed substrate using a composition containing metal particles so as to cover at least a portion of the roughened portion; sintering the metal particles in the metal particle-containing layer to form a sintered layer; A method for manufacturing an article, comprising:
Citation Information
Patent Citations
Fine coated copper particles and method for producing the same
JP2012072418A
Novel coated copper fine particle and production method thereof
JP2014148732A